Analysis of limb movement synchronization in primates locomotion - Sikorska-Piwowska, Zofia; Śliwka, Piotr; Ciszek, Bogdan (Anthropological Review, 2018)
The authors present an original mathematical model based on features identified with discrete variables using vector and hierarchical cluster analysis in primates locomotion. Proposed model allows to formalize and analyze the synchronization variability of movements in given locomotion types of adaptation and specialization in monkeys, apes and humans. The material covers observations of 102 forms including 9 species of primates: the chimpanzee, bonobo, orangutan, gibbon, gelada, mandrill, brown capuchin and ring–tailed lemur. The studies included also the synchronization of locomotory movements in man. The sequences of moves of pectoral and pelvic limbs, right and left, were studied in four categories: walking, running, jumping and brachiation. The locomotion movements depend on the brain centers and allow to find phylogenetic relations between examined forms in the evolution process. The knowledge of the pattern of movements is used in the treatment of paraplegia and paraparesis in humans.